Congenital Abdominal Aortic Aneurysm: A Case Report and Literature Review - Zhou, Zhibin; Yue, Yongqiang; Ma, Ke; Hua, Zhaohui; Li, Zhen (Frontiers in Pediatrics, 2022)
Congenital abdominal aortic aneurysm is a rare disease with unknown etiology, and the common symptoms are abdominal pulsatile mass and pain caused by aneurysm rupture. The disease has a high mortality rate and fewer reports of surgical treatment. Here, we present a case of an idiopathic congenital abdominal aortic aneurysm. A 4-year-old boy had an abdominal pulsatile mass, and computed tomography angiography revealed an isolated infrarenal abdominal aortic aneurysm. To prevent rupture of the aneurysm, we repaired the aneurysm with artificial graft transplantation. No genetic mutation of the known congenital aneurysmal diseases was found in the whole-exome sequencing of the patient and his parents. There was no graft obstruction, and the patient grew well 40 months after surgery. Open surgery is the best treatment for idiopathic congenital abdominal aortic aneurysms. Surgical details such as timing and graft selection need to be further explored.